A Potency And Challenge Of Warehouse Receipts System (Wrs) Implementation In Niaga Mukti Cooperation, Cianjur - Ukhwatul Khasanah; Dwidjono Hadi Darwanto; Slamet Hartono; Liana Fatma Leslie Pratiwi (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
Declining of agricultural commodity prices during the harvest season has become detrimental to farmers. It often makes farmers not harvest their crops because the cost of harvesting is more expensive than the selling price of the product. The government makes a Warehouse Receipt System (WRS) program to help farmer to solve the cost of farm business and anticipation of low price of farmer income in harvest time. The goal of the research is to analyze and to describe regarding the potency and challenge of warehouse receipts system implementation in Niaga Mukti Cooperation, Cianjur. The method used was descriptive analysis with the subject of Niaga Mukti Cooperation as the sample of WRS for rice commodity. The result of the research shows that warehouse receipts system has potency to become collateral credit document to obtain farming budgeting for the member of Niaga Mukti cooperation with 6% per year or 1,5% per month after receiving government grant. In conducting WRS program, the cooperation confronts various challenges such as economic society empowerment through WRS, warehouse empowerment receipts as alternative finance, finance instruments and agricultural marketing. However, it requires coordination and correlation among the government, regions, farm cooperation, endeavor and finance institutions.